Evaluation of the Expression and Prognosis of Neural‐Related Products Expressed by Cancer‐Derived Mesenchymal Stem Cells With the Characteristics of Neural Stem Cells - Liu Yongjun; Pan Zhiwen; Fu Shangui; Zhai Jinjie; Ying Rongbiao; Chen Zhongjian; Chen Wanyuan; Ju Haixing; Ma Dening; Long Dan; Luo Cong; Fu Zhixuan (Cancer Medicine, 2026)
ABSTRACT Studies have demonstrated that the nervous system plays an important role in cancer progression. Nevertheless, the effect of mesenchymal stem cells (MSCs) on cancer has yielded conflicting results. In this study, we discovered that cancer‐derived MSCs (CA‐MSCs) not only exhibit the properties of neural stem cells (NSCs) but also express a significant amount of neural‐related products. These products include neurotrophic factors, neuropeptides, synapse‐related products, and axon guidance factors. These identified products exhibit similar or different expression status among human NSCs, cancer and fat‐derived MSCs. CA‐MSCs expressed more BDNF , GDNF , and NGF than NSCs. Based on these neural‐related products expressed by CA‐MSCs, expression‐prognostic analysis was conducted. It revealed that the expression of MDK and MANF was higher in cancer, and the expression of BDNF , NPTX1 , and NGF increased as the tumor stage advanced. For ten neuropeptides, their expression levels were lower in cancer. Thirty synapse‐related products displayed their respective expression status between cancer and normal tissues. SYPL1 , SYBP2/3 , and STX4 had a significant impact on tumor prognosis. Higher levels of syntaxin‐4 , neugrin , and other axogenesis products were associated with a worse prognosis in cancer. Moreover, immunohistochemistry revealed that NSC‐like CA‐MSCs were abundant in cancer and exhibited a clear growth‐promoting effect on cancer. Briefly, CA‐MSCs, which are densely distributed in cancer and have the characteristics of NSCs, express a large number of nerve‐related products. These products may have significant effects on tumor progression and prognosis.